ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA DI JABODETABEK: PENDEKATAN SYSTEMATIC LITERATURE REVIEW - Tanjung, Risky Marchel (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
Mathematical problem-solving skills are essential for students, yet research indicates these skills remain low in the Jabodetabek area. This study aims to analyze the factors causing this issue and explore innovative learning approaches such as Problem-Based Learning (PBL) and Realistic Mathematics Education (PMR). The research method employed literature analysis, referencing various related studies. The findings reveal that low problem-solving skills stem from traditional teaching methods, low student motivation, limited use of technology, and inadequate learning facilities. PBL and PMR were proven effective in improving problem-solving abilities by actively engaging students and connecting mathematics to real-life contexts. In conclusion, implementing innovative approaches supported by teachers, technology, and educational policies can significantly enhance students' mathematical problem-solving skills.